1990
DOI: 10.1177/0741088390007003003
|View full text |Cite
|
Sign up to set email alerts
|

Teaching College Composition with Computers

Abstract: To understand the ways that teachers adapt writing instruction to a microcomputer classroom, the researchers observed and recorded activities minute-by-minute in four classes for a full semester of introductory composition. Two experienced teachers each taught two classes: one traditional class and one class that met for half of its time in a microcomputer classroom. This report contrasts their classes, calling attention to (a) the time pressures created by teaching with computers, (b) issues in training stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…• Computer classrooms to conventional classes, where the chalkboard, chalk, and perhaps overhead projectors are the primary conventional technologies, rarely documenting the specialized systems and technologies that define their "online" or Web-based experimental condition [45], [46];…”
Section: Assumptions About Effective Distance and Online Educationmentioning
confidence: 99%
“…• Computer classrooms to conventional classes, where the chalkboard, chalk, and perhaps overhead projectors are the primary conventional technologies, rarely documenting the specialized systems and technologies that define their "online" or Web-based experimental condition [45], [46];…”
Section: Assumptions About Effective Distance and Online Educationmentioning
confidence: 99%
“…Regarding quality issues, Bernhardt, Edwards, and Wojahn (1989) found that computer written college compositions were of better quality than those written by hand. On the other hand, Collier (1983b) found that the quality of writing did not improve when nursing students used the computer compared with their using conventional methods; however, the quantity of text written was greater.…”
mentioning
confidence: 99%
“…Since their writing experience and problems tend to be so varied, individualization of work in a computer writing lab set-up, with the teacher acting as tutor, may be an excellent arrangement for training the skills of non-native student writers. Moreover, as noted by Bernhardt, Wojahn, and Edwards (1990) and by Williamson and Pence (1989), the lab setting of many computer-assisted writing programs promotes the positive effects of increased individual attention and increased class time spent writing. The further possibility of networking on computer with other students as audience for their ideas and respondents to their writing adds an important new dimension for participation and communication (Eldred, 1989;Hartman et al, 1991;Levin, Riel, Rowe, and Boruta, 1985;Thrush and Hardisty, 1989) that can enhance communicative language teaching in the second language classroom.…”
Section: Setting Effectsmentioning
confidence: 93%